Optical Strategy Utilizing Contrast Modulation to Slow Myopia - James S. Wolffsohn, MBA, PhD; Kate L. Gifford, BAppSc (Optom), PhD (Ophthalmology Science)
A new method to slow myopia progression utilizes Diffusion Optics Technology (DOT) spectacle lenses. The proposed mechanism of action for the DOT lenses is to modulate contrast across the photoreceptor cells, leading to an altered activity of the ON and OFF pathways and slowing the progression of axial elongation. This approach is different from the current optical approaches that utilize optical defocus to reduce hyperopic defocus at the peripheral retina although central vision is fully corrected to slow myopia. Initial clinical studies with the DOT lenses have demonstrated promising results with a reduction in progression of myopia. This overview summarizes the current knowledge on myopia risk factors, the evidence for involvement of contrast signaling pathways in refractive error development, and the theories and mechanisms behind DOT lens technology. It also considers the role of contrast and the paradoxical observations given the established paradigm of form deprivation in animal models. Financial Disclosure(s): Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.